Neutrophil-Derived Proteases in the Microenvironment of Pancreatic Cancer -Active Players in Tumor Progression - Felix, Klaus (Int J Biol Sci, 2016)
A hallmark of pancreatic ductal adenocarcinoma (PDAC) is the fibro-inflammatory microenvironment, consisting of activated pancreatic stellate cells, extracellular matrix proteins, and a variety of inflammatory cells, such as T cells, macrophages, or neutrophils. Tumor-infiltrating immune cells, which are found in nearly all cancers, including PDAC, often fail to eliminate the tumor, but conversely can promote its progression by altering the tumor microenvironment. Pancreatic cancer cells are able to attract polymorphonuclear neutrophils (PMN) via tumor secreted chemokines and in human PDAC, PMN infiltrates can be observed in the vicinity of tumor cells and in the desmoplastic tumor stroma, which correlate with undifferentiated tumor growth and poor prognosis. The behavior of tumor-infiltrating neutrophils in the tumor micromilieu is not yet understood at a mechanistic level. It has been shown that PMN have the potential to kill tumor cells, either directly or by antibody-dependent cell-mediated cytotoxicity, but on the other side various adverse effects of PMN, such as promotion of aggressive tumor growth with epithelial-to-mesenchymal transition and increased metastatic potential, have been described. Recent therapeutic approaches for PDAC focus not only the tumor cell itself, but also elements of the tumor microenvironment. Therefore, the role of PMN and their derived products (e.g. cytokines, proteases) as a new vein for a therapeutic target should be critically evaluated in this context. This review summarizes the current understanding of the interplay between proteases of tumor-infiltrating neutrophils and pancreatic tumor cells and elements of the desmoplastic stroma.